Synthesis and Docking Study of 2–Aryl-4,5-diphenyl-1H-imidazole Derivatives as Lead Compounds for Antimalarial Agent - Ika Septiana; Bambang Purwono; Chairil Anwar; Beta Achromi Nurohmah; Jufrizal Syahri (Indonesian Journal of Chemistry, 2022)
Series of 2-aryl-4,5-diphenyl-1H-imidazole derivatives of 2-(4-hydroxy-3-methoxyphenyl)-4,5-diphenyl-1H-imidazole (1), 2-(4,5-dimethoxyphenyl)-4,5-diphenyl-1H-imidazole (2) and 2-(4-methoxyphenyl)-4,5-diphenyl-1H-imidazole (3) were produced and evaluated for their in vitro antimalarial activities against the chloroquine-sensitive Plasmodium falciparum 3D7 strain. A molecular docking study was also carried out against the crystal protein of Plasmodium falciparum dihydrofolate reductase-thymidylate synthase (PfDHFR-TS) (PDB ID: 1J3I.pdb) to predict the interaction between the compounds and protein. The physicochemical and pharmacokinetic parameters were computationally performed to predict the parameters of the absorption, distribution, metabolism, excretion, and toxicity (ADMET). Imidazoles were synthesized from aryl aldehyde derivatives with benzyl and ammonium acetate in glacial acetic acid using microwave-assisted-organic synthesis. Compounds 1, 2, and 3 were produced in 64.33, 50.56, and 70.55% yields, respectively. The IC50 of compounds 1, 2, and 3 against chloroquine-sensitive Plasmodium falciparum 3D7 strain was found to be 1.14, 5.28, and 2.42 µM, respectively. The molecular docking study agreed with the in vitro data by showing the lowest CDOCKER energy for compound 1 (-47.48 kcal/mol), followed by 3 (-43.79 kcal/mol) and 2 (-41.47 kcal/mol). The physicochemical and pharmacokinetic parameters showed that imidazoles 1, 2, and 3 obeyed Lipinski rules of five to propose as lead compounds for the antimalarial agents.